Graphene heat-conducting film and preparation method thereof
By adding metal oxides to graphene oxide slurry and performing heat treatment to create pores, the problems of low production capacity and environmental pollution of graphene thermal conductive films have been solved, achieving a high-efficiency and environmentally friendly increase in production efficiency.
Patent Information
- Application Number
- CN202511504344.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2026-02-06
AI Technical Summary
In existing graphene thermal conductive film preparation processes, the use of organic compounds to create pores results in poor capacity improvement and environmental pollution, and the capacity during the heat treatment stage is low.
Adding metal oxides such as ZnO, MnO, SnO2, Fe2O3, TiO2, and MoO2 to graphene oxide slurry can reduce foaming and improve film density and production efficiency by decomposing and creating pores during the heat treatment stage.
Without altering industrial equipment, this method increases the capacity of the heat treatment stage, reduces the complexity of the production process, achieves environmentally friendly production, maintains thermal conductivity, and increases the capacity of a single furnace.
Smart Images

Figure CN121470478A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of graphene thermal conductive film technology, specifically relating to a graphene thermal conductive film and its preparation method. Background Technology
[0002] Currently, the industrial manufacturing of graphene thermal conductive films typically involves coating graphene oxide and then reducing it to a graphene thermal conductive film through a heat treatment process. Patent CN115072709A, in an effort to improve the production capacity of graphene thermal conductive films, uses hydrazine-based reagents such as hydrazine hydrate and dimethylhydrazine to create pores in the graphene oxide film. However, this process is complex, has poor capacity improvement, and the organic compounds used are environmentally polluting. Summary of the Invention
[0003] To address the problems existing in the prior art, this invention provides a graphene thermally conductive film and its preparation method. This method can improve the production capacity of graphene thermally conductive films and does not use organic compounds, making it green and environmentally friendly.
[0004] In the current industrial manufacturing process of graphene thermally conductive films, the heat treatment stage is a critical phase, and improving actual production capacity must prioritize increasing the capacity of the heat treatment stage. This invention increases the single-furnace capacity by adding metal oxides to the graphene oxide slurry to improve the film density at each stage of heat treatment.
[0005] The present invention adopts the following technical solution: This invention provides a method for preparing a graphene thermally conductive film, comprising the following steps: (1) Preparation of graphene oxide slurry After the metal oxide powder is evenly dispersed with the aqueous dispersant, it is then mixed evenly with the graphene oxide dispersion solution. Finally, it is homogenized and defoamed to obtain the graphene oxide slurry. (2) Preparation of graphene oxide roll film The graphene oxide slurry from step (1) is coated onto the substrate, dried, and then the graphene oxide film is peeled off from the substrate and rolled up to obtain a graphene oxide roll film. (3) Preparation of graphene foam film The graphene oxide roll film is wound into a circular graphite boat and subjected to low-temperature heat treatment, high-temperature heat treatment and graphitization heat treatment in sequence to obtain a graphene foam film. (4) Preparation of graphene thermal conductive film The graphene foam film is continuously calendered to obtain a graphene thermally conductive film.
[0006] Preferably, in step (1), the metal oxide includes one or more of ZnO, MnO, SnO2, Fe2O3, TiO2, MoO2, and CuO, preferably one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2, and most preferably, the metal oxide is Fe2O3 and TiO2 in a molar ratio of 0.9:1.
[0007] Preferably, in step (1), the aqueous dispersant includes at least one of sodium carboxymethyl cellulose, nanocellulose, and polyacrylic acid.
[0008] Preferably, in step (1), the content of graphene oxide is 90%-99.9% of the total solid content of the slurry, and the content of metal oxide is 0.1%-10% of the total solid content of the slurry; in the graphene oxide slurry, the final total solid content of the slurry is 3%-6%, and the viscosity is 10000-80000 mPa·s; Preferably, the graphene oxide content is 93%-99% of the total solid content of the slurry, and the metal oxide content is 1%-7% of the total solid content of the slurry; the final total solid content of the graphene oxide slurry is 4.5%-4.8%.
[0009] Preferably, in step (2), the gap of the coating is 3500-4000 μm and the coating temperature is 50-60℃.
[0010] Preferably, in step (3), When winding, a gap must be left between each turn, and the gap should gradually decrease from the inside to the outside. For example, the gap between each turn in the first 1 / 3 of the roll length is 1.5-3.8cm, the gap between each turn in the middle 1 / 3 of the roll length is 1-2.8cm, and the gap between each turn in the outermost 1 / 3 of the roll length is 0.5-2cm. Before high-temperature heat treatment, the roll film is rewound so that the gap between each turn is 0-2.3cm. Preferably, when the metal oxide is one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2, during winding, the gap between each turn in the first 1 / 3 of the length of the roll is 1.5-3cm, the gap between each turn in the middle 1 / 3 of the length is 1-2cm, and the gap between each turn in the outermost 1 / 3 of the length is 0.5-1.2cm; before high-temperature heat treatment, the roll film is rewound so that the gap width between each turn is fixed at 0-1.5cm.
[0011] Preferably, in step (3), The low-temperature heat treatment is as follows: heat-treating the graphene oxide roll film at 200℃-400℃ for 24-120h, and then naturally cooling it to room temperature; The high-temperature heat treatment is as follows: the graphene oxide roll film is heat-treated at 800℃-1500℃ for 24-120 hours and then naturally cooled to room temperature; The graphitization heat treatment is as follows: the graphene oxide roll film is heat-treated at 2400-3300℃ for 24-120h and then naturally cooled to room temperature.
[0012] Preferably, in step (3), the density of the graphene foam film is: After low-temperature heat treatment, the density is 0.45-0.90 g / cm³. 3 Preferably, after low-temperature heat treatment, the density is 0.50-0.90 g / cm³. 3 ; After high-temperature heat treatment, the density is 0.35-0.80 g / cm³. 3 Preferably, after high-temperature heat treatment, the density is 0.40-0.80 g / cm³. 3 ; After graphitization heat treatment, the density is 0.40-0.80 g / cm³. 3 Preferably, after graphitization heat treatment, the density is 0.45-0.80 g / cm³. 3 .
[0013] The present invention also provides a graphene thermal conductive film, which is prepared by any of the above preparation methods.
[0014] Preferably, the density of the graphene thermally conductive film is 2.10-2.20 g / cm³. 3 The thermal conductivity is 1350-1650 W / (m·K); preferably 1420-1650 W / (m·K).
[0015] The beneficial effects of this invention are as follows: (1) In this invention, metal oxides are added during the preparation of graphene oxide slurry. During heat treatment, the metal oxides decompose to create pores, which creates channels for the gas that needs to be discharged during heat treatment of graphene oxide. This reduces the foaming phenomenon during the heat treatment stage, which can not only increase the density at low temperature, high temperature and graphitization stages, but also increase the length of the roll material in the boat while maintaining the continuity of the roll material, thereby increasing the actual production capacity (the production capacity of graphene film is calculated by area. During the heat treatment stage, the film weight is the same, the area is the same, the higher the density, the smaller the volume, so the thickness of the film in the boat is smaller. The volume of the circular graphite boat is fixed. By suppressing foaming and increasing density, the space reserved for roll material foaming in the boat is reduced, resulting in an increase in the length of the roll material loaded in a single furnace and an increase in the total area loaded in the boat, ultimately showing an increase in the actual heat treatment capacity). This fundamentally solves the problem of low production capacity in the heat treatment stage in the existing preparation process.
[0016] During low-temperature heat treatment, most of the oxygen-containing groups in graphene oxide are broken down. The film surface is most brittle and susceptible to damage after high-temperature treatment, so the roll material should not be tightened during the high-temperature stage.
[0017] Oxide-containing groups exist in graphene oxide and are released as gas, without creating pores. The heat treatment stage primarily involves removing these oxygen-containing groups and rearranging carbon atoms to repair defects, during which gas escapes. To ensure the integrity of the roll structure, the interval between each turn is relatively large, severely impacting production capacity. Therefore, this invention incorporates metal oxides (capable of creating pores between 500-1000℃) to create pores, increase venting channels, and reduce foaming, thereby increasing production capacity.
[0018] (2) This invention can improve the production capacity and appearance of the heat treatment stage without changing the original industrial equipment, thereby increasing production capacity and reducing the complexity of the production process. It is highly feasible in industry.
[0019] (3) No organic compounds are added during the production process of this invention, which is not only environmentally friendly, but also avoids the impact of these materials on the thermal conductivity of the finished graphene thermal conductive film. Attached Figure Description
[0020] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1A This is a simplified structural diagram of a circular graphite boat-shaped dish. Figure 1B This is a simplified diagram of a graphene oxide roll film wound into a circular graphite boat. In the diagram, 1 is the top cover of the graphite boat, 2 is a graphite column, 3 is the bottom plate of the graphite boat, 4 is the graphene oxide roll film, and 5 is a graphite cylinder.
[0021] Figure 2 SEM characterization of the graphene thermal conductive film surface.
[0022] Figure 3A and Figure 3B EDS spectrum analysis of pores on the surface of graphene thermal conductive film.
[0023] Figure 4A The dispersion of ZnO in CNF dispersion; Figure 4B This shows the dispersion of ZnO in H2O.
[0024] Figure 5 The surface of the graphene thermally conductive film with added ZnO-H2O dispersion. Detailed Implementation
[0025] The following examples are provided to better understand the present invention, but do not limit the invention. Unless otherwise specified, the experimental methods in the following examples are conventional methods. Unless otherwise specified, the experimental materials used in the following examples were purchased from conventional biochemical reagent companies. All quantitative experiments in the following examples were performed in triplicate, and the results were averaged.
[0026] The method for preparing the graphene thermally conductive film of the present invention includes the following steps: (1) Preparation of graphene oxide slurry After the metal oxide powder is evenly dispersed with the aqueous dispersant, it is then mixed evenly with the graphene oxide dispersion solution, and homogenized and defoamed by a homogenizer to obtain the graphene oxide slurry.
[0027] (2) Preparation of graphene oxide roll film The graphene oxide slurry from step (1) is coated onto the substrate, dried, and then the graphene oxide film is peeled off from the substrate and rolled up to obtain a graphene oxide roll film.
[0028] (3) Preparation of graphene foam film The graphene oxide roll film is wound into a circular graphite boat and heat-treated to obtain a graphene foam film.
[0029] (4) Preparation of graphene thermal conductive film The graphene foam film is continuously calendered to obtain a graphene thermally conductive film.
[0030] Regarding step (1): In this invention, graphene oxide filter cake is mixed evenly with deionized water to obtain the graphene oxide dispersion solution.
[0031] In this invention, graphene oxide accounts for 90%-99.9% of the total solid content of the slurry, preferably 93%-99%, and the final total solid content of the slurry is 3%-6%, preferably 4.5%-4.8%, with a final slurry viscosity of 10000-80000 mPa·s. The solid content of the graphene oxide filter cake in the total slurry affects the slurry viscosity and is related to the subsequent coating state.
[0032] The final total solids content of the slurry refers to the percentage of the mass of solid components in the slurry relative to the total mass of the slurry.
[0033] The final viscosity of the slurry refers to the viscosity value measured after the slurry is prepared.
[0034] In this invention, the metal oxide includes one or more of zinc oxide (ZnO), manganese oxide (MnO), tin oxide (SnO2), iron oxide (Fe2O3), titanium oxide (TiO2), molybdenum oxide (MoO2), and copper oxide (CuO), preferably one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2.
[0035] The above-mentioned metal oxides were chosen because they can be removed in the temperature range of 500-1000℃.
[0036] The five metal oxides ZnO, SnO2, Fe2O3, TiO2, and MoO2 can be effectively reduced, decomposed, or volatilized in the key temperature range (500-1000℃) and typical atmosphere (reducing) of graphene thermal reduction. The removal process is accompanied by gas generation or significant volume change, thereby achieving pore formation. At the same time, the residues after removal are minimal or have good thermal conductivity and / or catalytic graphitization effect, thus improving the thermal conductivity while ensuring high density.
[0037] In this invention, the particle size requirement for all metal oxides is nanoscale powder. The reason is that nanoscale metal oxides create smaller pore diameters, which, after thorough and uniform dispersion, can reduce foaming, increase density at each heat treatment stage, and without reducing the final thermal conductivity. Since all particles are nanoscale, the particle size of the metal oxides will not be specifically described in the following embodiments and comparative examples.
[0038] In this invention, the aqueous dispersant is an anionic dispersant, preferably sodium carboxymethyl cellulose (CMC), nanocellulose (CNF), and polyacrylic acid (PAA).
[0039] The reasons for choosing these three are as follows: Graphene oxide contains a large number of oxygen-containing functional groups on its surface, which are negatively charged. To maintain the uniformity of slurry dispersion, an aqueous anionic dispersant is selected. These three are also chosen because they are low in cost, readily available, safe and environmentally friendly, and have extremely low sulfur content, which will not reduce the thermal conductivity of the graphene thermal conductive film.
[0040] In this invention, the aqueous dispersant accounts for 0.001-0.006% of the total solid content of the slurry, for example, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, or 0.006%. When used, it can be prepared as an aqueous solution with a weight percentage concentration of 1%.
[0041] If the amount of water-based dispersant is too low, it will not be able to disperse the metal oxides. If the amount is too high, it will increase the viscosity. Moreover, its function is only to disperse the metal oxides and will not optimize the dispersibility of the slurry.
[0042] In this invention, the metal oxides preferably account for 0.1%-10% of the total solid content of the slurry, such as 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, and more preferably 1%-7%.
[0043] A concentration above 10% will result in excessive porosity, reducing thermal conductivity; a concentration below 0.1% has a negligible effect and little impact on density. Within the preferred range (1-7%), the porosity is uniformly dispersed, effectively creating ventilation channels without negatively affecting thermal conductivity.
[0044] In this invention, the homogenization process opens up the graphene oxide sheets, allowing for further mixing of the slurry.
[0045] Regarding step (2): In this invention, there are no special restrictions on the type of substrate. Commonly used substrates on the market can be selected. Preferably, the substrate material is one or more of polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE), polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), copper foil, aluminum film, and glass.
[0046] In this invention, there are no special restrictions on the coating method of applying graphene oxide slurry to the substrate; any conventional coating method in the field, such as scraping, is acceptable.
[0047] In this invention, the coating gap (i.e., coating thickness) is preferably 1000-10000μm, for example, 1000μm, 2000μm, 3000μm, 3500μm, 3800μm, 4000μm, 5000μm, 6000μm, 7000μm, 8000μm, 9000μm, 10000μm; the coating temperature is preferably 35-85℃, for example, 35℃, 40℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃.
[0048] As a preferred embodiment, the gap of the coating is 3500-4000μm, and the coating temperature is 50-60℃.
[0049] Regarding step (3): A simplified structural diagram of a circular graphite boat is shown below. Figure 1A There is a graphite pillar 2 in the middle of the graphite boat. The bottom of the graphite pillar 2 is connected and fixed to the bottom plate 3 of the graphite boat through threads. The top of the graphite pillar 2 is connected and fixed to the top cover plate 1 of the graphite boat through threads.
[0050] In this invention, the specific method for winding the graphene oxide roll film into a circular graphite boat is as follows: The graphene oxide roll film 4 is wound around the graphite pillar 2 in a circular graphite boat, and a graphite cylinder 5 is used to fix the outermost side of the graphene oxide roll film. The top cover plate 1 of the graphite boat is then placed on top, thereby further restricting the foaming of the graphene oxide roll film during the heat treatment stage.
[0051] Figure 1A This is a simplified structural diagram of a circular graphite boat-shaped dish. Figure 1B This is a simplified diagram of a graphene oxide roll film wound into a circular graphite boat.
[0052] In some implementations, during winding, gaps must be left between each turn to facilitate hole formation, and the gaps gradually decrease from the inside to the outside. For example, the gap between each turn in the first 1 / 3 of the roll length is 1.5-3.8cm, the gap between each turn in the middle 1 / 3 of the roll length is 1-2.8cm, and the gap between each turn in the outermost 1 / 3 of the roll length is 0.5-2cm. Before high-temperature heat treatment, the roll film is rewound so that the gap between each turn is 0-2.3cm.
[0053] In some embodiments, when the metal oxide is one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2, during winding, a gap must be left between each turn to facilitate hole formation, and the gap gradually decreases from the inside to the outside. For example, the gap between each turn in the first 1 / 3 of the roll length is 1.5-3cm, the gap between each turn in the middle 1 / 3 of the roll length is 1-2cm, and the gap between each turn in the outermost 1 / 3 of the roll length is 0.5-1.2cm. Before high-temperature heat treatment, the roll film is rewound so that the gap width between each turn is fixed at 0-1.5cm.
[0054] In this invention, the heat treatment is as follows: the graphene oxide roll film is first subjected to low-temperature heat treatment, then to high-temperature heat treatment, and finally to graphitization heat treatment.
[0055] The preferred low-temperature heat treatment involves placing the graphene oxide roll film in a low-temperature furnace at 200℃-400℃ for 24-120 hours, followed by natural cooling to room temperature. For example, heat treatments can be performed at 200℃, 250℃, 300℃, 350℃, and 400℃ for 24 hours, 48 hours, 72 hours, 96 hours, and 120 hours, respectively.
[0056] The reason for choosing the above temperature and time is to decompose oxygen-containing groups. In order to ensure that all the roll film in the boat can undergo the decomposition reaction of oxygen-containing groups, the holding time is longer, which can make the oxygen-containing groups basically removed.
[0057] The preferred high-temperature heat treatment involves placing the graphene oxide roll film in a high-temperature furnace at 800℃-1500℃ for 24-120 hours, followed by natural cooling to room temperature. For example, heat treatment at 800℃, 900℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, and 1500℃ for 24 hours, 48 hours, 72 hours, 96 hours, and 120 hours, respectively.
[0058] The reason for choosing the above temperature and time is that at this temperature, oxygen-containing groups and metal oxides can be further removed. The pores created by the removal of metal oxides become pathways for gas to escape, reducing the degree of foaming and increasing density.
[0059] The preferred graphitization heat treatment involves placing the graphene oxide roll film in a graphitization furnace at 2400-3300℃ for 24-120 hours, followed by natural cooling to room temperature. For example, heat treatment can be performed at 2400℃, 2500℃, 2600℃, 2700℃, 2800℃, 2900℃, 3000℃, 3100℃, 3200℃, and 3300℃ for 24 hours, 48 hours, 72 hours, 96 hours, and 120 hours, respectively.
[0060] The reason for choosing the above temperature and time is that at this temperature, further directional alignment and carbon atom rearrangement are possible, resulting in a near-ideal lattice structure. Carbon atom rearrangement is a slow process that needs to be completed over a long period at the graphitization temperature to achieve optimal thermal performance.
[0061] In this invention, after the above heat treatment, the density of the graphene foam film is: After low-temperature heat treatment, the density is 0.45-0.90 g / cm³. 3 For example, a density of 0.45 g / cm³ 3 0.58g / cm 3 0.68 g / cm 3 0.78 g / cm 3 0.90 g / cm 3 .
[0062] After high-temperature heat treatment, the density is 0.35-0.80 g / cm³. 3 For example, a density of 0.35 g / cm³ 3 0.49 g / cm 3 0.59g / cm 3 0.69 g / cm 3 0.75g / cm 3 0.80 g / cm 3 .
[0063] After graphitization heat treatment, the density is 0.40-0.80 g / cm³. 3 For example, a density of 0.40 g / cm³3 0.50g / cm 3 0.60 g / cm 3 0.66 g / cm 3 0.80 g / cm 3 .
[0064] When the metal oxide is one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2, the density of the graphene foam film after the above heat treatment is: After low-temperature heat treatment, the density is 0.50-0.90 g / cm³. 3 .
[0065] After high-temperature heat treatment, the density is 0.40-0.80 g / cm³. 3 .
[0066] After graphitization heat treatment, the density is 0.45-0.80 g / cm³. 3 .
[0067] Regarding step (4): In this invention, the calendering pressure is preferably 100-500 MPa; for example, 100 MPa, 200 MPa, 300 MPa, 400 MPa, 500 MPa.
[0068] The graphene thermally conductive film prepared using the method of this invention has a thickness of 39-43 μm, an average pore size of 0.7-1.0 μm, and a density of 2.10-2.20 g / cm³. 3 The thermal conductivity is 1350-1650 W / (m·K); the single-furnace production capacity of graphene foam film preparation steps is 270-520 m³. 2 .
[0069] When the metal oxide is one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2, the thermal conductivity of the graphene thermally conductive film prepared by the method of this invention is 1524-1579 W / (m·K); the single-furnace capacity of the graphene foam film preparation steps is 340-520 m³ / s. 2 .
[0070] In this invention, the testing methods for various performance indicators are as follows: The thermal diffusivity test follows ASTM E1461, "Standard Test Method for Determining Fixed Thermal Conductivity by the Flash Method," and uses LASER-FLASH. Samples are cut into 25.4 mm diameter discs. Based on the principle of the laser flash method, the thermal conductivity (all thermal conductivity values are measured in the X and Y directions) is calculated using the formula: Thermal conductivity = Thermal diffusivity * Density * Specific heat capacity. Density is tested using the volumetric method. The average pore size is measured using SEM.
[0071] Example 1: Preparation of graphene thermally conductive film (1) Preparation of graphene oxide slurry 4.278 kg of graphene oxide filter cake (dry basis) was added to deionized water and stirred until homogeneous to obtain 90 kg of graphene oxide dispersion solution. 0.207 kg of Fe2O3 powder and 0.115 kg of TiO2 powder were added to 0.5 kg of uniform 1% nanocellulose (CNF) aqueous solution and stirred until homogeneous. Then, the mixture was added to the graphene oxide dispersion solution. Finally, deionized water was added to make the final total slurry weight 100 kg. The mixture was stirred until homogeneous and defoamed using a homogenizer to obtain graphene oxide slurry. The final slurry has an overall solid content of 4.6% and a viscosity of 41,000 mPa·s; Fe2O3 accounts for 4.5% of the final slurry solid content, and TiO2 accounts for 2.5% of the final slurry solid content.
[0072] (2) Preparation of graphene oxide roll film The above slurry was coated using a coating machine with PP as the substrate, a coating gap of 3500 μm, and a coating temperature of 55℃. A dense graphene oxide roll film was then produced through continuous coating, peeling, and winding processes.
[0073] (3) Preparation of graphene foam film In this embodiment, the diameter of the space inside the circular graphite boat that can accommodate the rolled material is 600mm, and the height is 200mm. The wall thickness of the graphite cylinder is 20mm, the thickness of the bottom plate of the boat is 40mm, the thickness of the top cover plate is 30mm, and the diameter of the graphite column is 40mm.
[0074] To ensure the structural integrity of the roll material, the graphene oxide roll film was wound into a circular graphite boat, from the inside out. The starting end was attached to a graphite pillar. The gap between each turn was 1.5 cm for the first 1 / 3 of the roll length, 1 cm for the middle 1 / 3, and 0.5 cm for the outermost 1 / 3. After winding, a graphite cylinder was placed on the outermost layer of the roll. Since no carbon paper was used for heat transfer in the roll material, a low-temperature furnace with top and bottom ventilation was used for 400℃ low-temperature treatment for 96 hours to improve temperature transfer. After cooling to room temperature, the density was tested and found to be 0.84 g / cm³. 3 The roll of film, after being cooled to low temperature in the boat, was tightened so that each turn was perfectly adhered. The film, after being cooled to low temperature, was then placed in a high-temperature furnace at 900℃ for 72 hours. After cooling to room temperature, its density was tested and found to be 0.75 g / cm³. 3 The membrane, after being subjected to high temperature, was placed in a graphitization furnace at 3100℃ for 96 hours. After cooling to room temperature, a graphene foam membrane was obtained, and its density was measured to be 0.78 g / cm³. 3 .
[0075] In this embodiment, the metal oxide is a certain proportion of Fe2O3 and TiO2 powder. Under this proportion, sufficient pores can be formed during high-temperature heat treatment. Due to the creation of gas exhaust channels, the expansion degree of the roll film is low during the high-temperature and graphitization stages. The roll film can be directly tightened to fit each turn perfectly during the high-temperature stage, and the whole roll of graphene foam film obtained after graphitization treatment does not break.
[0076] (4) Preparation of graphene thermal conductive film The graphene foam film is calendered using a roller press with a pressure of 450 MPa to obtain a graphene thermal conductive film.
[0077] SEM and EDS characterization analysis of the graphene thermally conductive film revealed the presence of pores on the film surface (such as...). Figure 2 As shown), and the membrane surface is free of impurities (such as...). Figure 3A and Figure 3B As shown in the figure, this proves that the metal oxide has successfully created pores in the graphene thermal conductive film and has been completely decomposed, reducing foaming and increasing density to achieve increased production capacity.
[0078] Figure 2 SEM characterization of the graphene thermal conductive film surface.
[0079] Figure 3A and Figure 3B EDS spectrum analysis of pores on the surface of graphene thermal conductive film.
[0080] Testing revealed that the graphene thermally conductive film had a thickness of 43 μm, an average pore size of 0.8 μm, and a density of 2.16 g / cm³. 3 With a thermal conductivity of 1610 W / (m·K), the single-furnace capacity of graphene foam film preparation has been increased to 515 m³ / s. 2 .
[0081] Example 2: Preparation of graphene thermal conductive film (1) Preparation of graphene oxide slurry 4.608 kg of graphene oxide filter cake (dry basis) was added to deionized water and stirred until homogeneous to obtain 90 kg of graphene oxide dispersion solution; 0.192 kg of ZnO powder was added to 0.5 kg of 1% CNF (nanocellulose) aqueous solution and stirred until homogeneous. Figure 4A After that, add it to the graphene oxide dispersion solution, and finally add deionized water to make the final total slurry weight 100kg. Mix it evenly, and then homogenize and defoam it through a homogenizer to obtain the graphene oxide slurry. The final slurry has an overall solid content of 4.8% and a viscosity of 42,000 mPa·s; ZnO accounts for 4% of the final slurry's solid content.
[0082] Figure 4AThis shows the dispersion of ZnO in CNF dispersion.
[0083] (2) Preparation of graphene oxide roll film The above slurry was coated using a coating machine with PP as the substrate, a coating gap of 3800 μm, and a coating temperature of 55℃. A dense graphene oxide roll film was then produced through continuous coating, peeling, and winding processes.
[0084] (3) Preparation of graphene foam film The difference between this step and Example 1 is as follows: the winding method is as follows: the gap between each turn of the first 1 / 3 of the roll length is 3cm, the gap between each turn of the middle 1 / 3 of the roll length is 2cm, and the gap between each turn of the outermost 1 / 3 of the roll length is 1.2cm. After winding, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature range, the roll is tightened with a gap of 1.5cm between each turn. The rest of this step is the same as in Example 1.
[0085] Measurements showed that the density after low-temperature treatment was 0.54 g / cm³. 3 The density after high-temperature treatment is 0.43 g / cm³. 3 The density after graphitization treatment is 0.47 g / cm³. 3 .
[0086] In this embodiment, the metal oxide is ZnO, which can partially create pores during the high-temperature heat treatment stage. The roll film will expand slightly during the high-temperature stage and the graphitization stage. Therefore, in this embodiment, when the roll is tightened before entering the high temperature stage, a gap needs to be left for each turn so that the whole roll of graphene foam film obtained after graphitization treatment will not break.
[0087] (4) The preparation steps of the graphene thermal conductive film are the same as in Example 1.
[0088] The graphene thermal conductive film prepared in this embodiment was characterized by SEM and EDS. The results were similar to those in Example 1. There were pores on the film surface and no impurities on the film surface, so the corresponding figures are omitted.
[0089] Testing revealed that the graphene thermally conductive film has a thickness of 41 μm, an average pore size of 1.0 μm, and a density of 2.15 g / cm³. 3 The thermal conductivity is 1425 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation process is 340 m³. 2 .
[0090] Example 3: Preparation of graphene thermally conductive film (1) Preparation of graphene oxide slurry 4.512 kg of graphene oxide filter cake (dry basis) was added to deionized water and stirred until homogeneous to obtain 90 kg of graphene oxide dispersion solution. 0.144 kg of Fe2O3 powder and 0.144 kg of TiO2 powder were added to 0.5 kg of 1% polyacrylic acid (PAA) aqueous solution and stirred until homogeneous. Then, the mixture was added to the graphene oxide dispersion solution. Finally, deionized water was added to make the final total slurry weight 100 kg. The mixture was homogenized and defoamed using a homogenizer to obtain graphene oxide slurry. The final slurry has an overall solid content of 4.8% and a viscosity of 41,500 mPa·s; Fe2O3 accounts for 3% of the final slurry solid content, and TiO2 accounts for 3% of the final slurry solid content.
[0091] (2) The preparation steps of the graphene oxide roll film are the same as in Example 2.
[0092] (3) Preparation of graphene foam film The difference between this step and Example 1 is as follows: the winding method is as follows: the gap between each turn of the roll is 2.2 cm for the first 1 / 3 of the roll length, 1.6 cm for the middle 1 / 3 of the roll length, and 0.9 cm for the outermost 1 / 3 of the roll length. After winding, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high-temperature zone, the roll is tightened, with a gap of 0.7 cm between each turn. The rest of this step is the same as in Example 1.
[0093] Measurements showed that the density after low-temperature treatment was 0.65 g / cm³. 3 The density after high-temperature treatment is 0.55 g / cm³. 3 The density after graphitization treatment is 0.59 g / cm³. 3 .
[0094] In this embodiment, the metal oxide is a certain proportion of Fe2O3 and TiO2 powder. Under this proportion, partial pore formation can be achieved during the high-temperature heat treatment stage. The roll film will expand slightly during the high-temperature stage and the graphitization stage. Therefore, in this embodiment, when the roll is tightened before entering the high temperature, a gap needs to be left for each turn. The whole roll of graphene foam film obtained after graphitization treatment will not break.
[0095] (4) The preparation steps of the graphene thermal conductive film are the same as in Example 1.
[0096] The graphene thermal conductive film prepared in this embodiment was characterized by SEM and EDS. The results were similar to those in Example 1. There were pores on the film surface and no impurities on the film surface, so the corresponding figures are omitted.
[0097] Testing revealed that the graphene thermally conductive film had a thickness of 41 μm, an average pore size of 0.8 μm, and a density of 2.14 g / cm³. 3The thermal conductivity is 1470 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation process is 400 m³. 2 .
[0098] Example 4: Preparation of graphene thermal conductive film (1) Preparation of graphene oxide slurry 4.365 kg of graphene oxide filter cake (dry basis) was added to deionized water and stirred until homogeneous to obtain 90 kg of graphene oxide dispersion solution. 0.135 kg of Fe2O3 powder was added to 0.5 kg of 1% sodium carboxymethyl cellulose (CMC) aqueous solution and stirred until homogeneous. Then, it was added to the graphene oxide dispersion solution. Finally, deionized water was added to make the final total slurry weight 100 kg. The mixture was homogenized and defoamed using a homogenizer to obtain graphene oxide slurry. The final slurry has an overall solid content of 4.5% and a viscosity of 40,000 mPa·s; Fe2O3 accounts for 3% of the final slurry's solid content.
[0099] (2) Preparation of graphene oxide roll film The above slurry was coated using a coating machine with PP as the substrate, a coating gap of 4000 μm, and a coating temperature of 55℃. A dense graphene oxide roll film was then produced through continuous coating, peeling, and winding processes.
[0100] (3) Preparation of graphene foam film The difference between this step and Example 1 is as follows: the winding method is as follows: the gap between each turn of the roll is 1.8 cm for the first 1 / 3 of the roll length, 1.2 cm for the middle 1 / 3 of the roll length, and 0.6 cm for the outermost 1 / 3 of the roll length. After winding, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high-temperature zone, the roll is tightened, with a gap of 0.2 cm between each turn. The rest of this step is the same as in Example 1.
[0101] Measurements showed that the density after low-temperature treatment was 0.71 g / cm³. 3 The density after high-temperature treatment is 0.66 g / cm³. 3 The density after graphitization treatment is 0.67 g / cm³. 3 .
[0102] In this embodiment, the metal oxide is Fe2O3, which can partially create pores during the high-temperature heat treatment stage. The roll film will expand slightly during the high-temperature stage and the graphitization stage. Therefore, in this embodiment, when the roll is tightened before entering the high temperature stage, a gap needs to be left for each turn so that the whole roll of graphene foam film obtained after graphitization treatment will not break.
[0103] (4) The preparation steps of the graphene thermal conductive film are the same as in Example 1.
[0104] The graphene thermal conductive film prepared in this embodiment was characterized by SEM and EDS. The results were similar to those in Example 1. There were pores on the film surface and no impurities on the film surface, so the corresponding figures are omitted.
[0105] Testing revealed that the graphene thermally conductive film had a thickness of 42 μm, an average pore size of 0.7 μm, and a density of 2.12 g / cm³. 3 The thermal conductivity is 1570 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation process is 470 m³. 2 .
[0106] Example 5: Preparation of graphene thermal conductive film The difference between this embodiment and Embodiment 1 is that: (1) Replace Fe2O3 powder and TiO2 powder with MoO2 powder; MoO2 accounts for 6% of the final slurry solid content. Among them, the dry weight of graphene oxide filter cake is 4.324 kg and the weight of MoO2 powder is 0.276 kg.
[0107] (2) The preparation steps of the graphene foam film are as follows: the gap between each turn of the first 1 / 3 of the length of the roll is 2cm, the gap between each turn of the middle 1 / 3 of the length is 1.5cm, and the gap between each turn of the outermost 1 / 3 of the length is 0.8cm. After the roll is finished, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature, the roll is tightened with a gap of 0.5cm between each turn.
[0108] The remaining steps and parameters are the same as in Example 1.
[0109] The density of the graphene foam film was measured to be 0.67 g / cm³ after low-temperature treatment. 3 The density after high-temperature treatment is 0.57 g / cm³. 3 The density after graphitization treatment is 0.60 g / cm³. 3 .
[0110] In this embodiment, the metal oxide is MoO2, which can partially create pores during the high-temperature heat treatment stage. The roll film will expand slightly during the high-temperature stage and the graphitization stage. Therefore, in this embodiment, when the roll is tightened before entering the high temperature stage, a gap needs to be left for each turn so that the whole roll of graphene foam film obtained after graphitization treatment will not break.
[0111] The graphene thermal conductive film prepared in this embodiment was characterized by SEM and EDS. The results were similar to those in Example 1. There were pores on the film surface and no impurities on the film surface, so the corresponding figures are omitted.
[0112] The graphene thermally conductive film has a thickness of 40 μm, an average pore size of 1.0 μm, and a density of 2.14 g / cm³. 3The thermal conductivity is 1540 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation steps is 430 m³. 2 .
[0113] Example 6: Preparation of graphene thermal conductive film The difference between this embodiment and Embodiment 1 is that: (1) Replace Fe2O3 powder and TiO2 powder with 0.322 kg SnO2 powder; SnO2 accounts for 7% of the final slurry solid content.
[0114] (2) The preparation steps of the graphene foam film are as follows: the gap between each turn of the first 1 / 3 of the length of the roll is 2.2 cm, the gap between each turn of the middle 1 / 3 of the length is 1.6 cm, and the gap between each turn of the outermost 1 / 3 of the length is 0.9 cm. After the roll is finished, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature, the roll is tightened with a gap of 0.8 cm between each turn.
[0115] The remaining steps and parameters are the same as in Example 1.
[0116] Measurements showed that the density of the graphene foam film after low-temperature treatment was 0.65 g / cm³. 3 The density after high-temperature treatment is 0.53 g / cm³. 3 The density after graphitization treatment is 0.57 g / cm³. 3 .
[0117] In this embodiment, the metal oxide is SnO2, which can partially create pores during the high-temperature heat treatment stage. The roll film will expand slightly during the high-temperature stage and the graphitization stage. Therefore, in this embodiment, when the roll is tightened before entering the high temperature stage, a gap needs to be left for each turn so that the whole roll of graphene foam film obtained after graphitization treatment will not break.
[0118] The graphene thermal conductive film prepared in this embodiment was characterized by SEM and EDS. The results were similar to those in Example 1. There were pores on the film surface and no impurities on the film surface, so the corresponding figures are omitted.
[0119] The graphene thermally conductive film has a thickness of 39 μm, an average pore size of 0.9 μm, and a density of 2.14 g / cm³. 3 The thermal conductivity is 1450 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation steps is 390 m³. 2 .
[0120] Example 7: Preparation of graphene thermally conductive film The difference between this embodiment and Embodiment 1 is that: (1) Replace Fe2O3 powder and TiO2 powder with MnO powder; MnO accounts for 6% of the final slurry solid content. Among them, the dry weight of graphene oxide filter cake is 4.324 kg and the weight of MnO powder is 0.276 kg.
[0121] (2) The preparation steps of the graphene foam film are as follows: the gap between each turn of the first 1 / 3 of the length of the roll is 3.5cm, the gap between each turn of the middle 1 / 3 of the length is 2.5cm, and the gap between each turn of the outermost 1 / 3 of the length is 1.8cm. After the roll is finished, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature, the roll is tightened with a gap of 2cm between each turn.
[0122] The remaining steps and parameters are the same as in Example 1.
[0123] Measurements showed that the density of the graphene foam film after low-temperature treatment was 0.50 g / cm³. 3 The density after high-temperature treatment is 0.40 g / cm³. 3 The density after graphitization treatment is 0.44 g / cm³. 3 .
[0124] In this embodiment, the metal oxide is MnO, which can partially create pores during the high-temperature heat treatment stage. The roll film will expand slightly during the high-temperature stage and the graphitization stage. Therefore, in this embodiment, when the roll is tightened before entering the high temperature stage, a gap needs to be left for each turn so that the whole roll of graphene foam film obtained after graphitization treatment will not break.
[0125] The graphene thermal conductive film prepared in this embodiment was characterized by SEM and EDS. The results were similar to those in Example 1. There were pores on the film surface and no impurities on the film surface, so the corresponding figures are omitted.
[0126] The graphene thermally conductive film has a thickness of 40 μm, an average pore size of 1.0 μm, and a density of 2.15 g / cm³. 3 The thermal conductivity is 1420 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation steps is 290 m³. 2 .
[0127] Example 8: Preparation of graphene thermal conductive film The difference between this embodiment and Embodiment 1 is that: (1) Replace Fe2O3 powder and TiO2 powder with 0.322 kg CuO powder; CuO accounts for 7% of the final slurry solid content.
[0128] (2) The preparation steps of the graphene foam film are as follows: the gap between each turn of the first 1 / 3 of the length of the roll is 3.8 cm, the gap between each turn of the middle 1 / 3 of the length is 2.8 cm, and the gap between each turn of the outermost 1 / 3 of the length is 2 cm. After the winding is completed, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature, the roll is tightened with a gap of 2.3 cm between each turn.
[0129] The remaining steps and parameters are the same as in Example 1.
[0130] Measurements showed that the density of the graphene foam film after low-temperature treatment was 0.48 g / cm³. 3 The density after high-temperature treatment is 0.39 g / cm³. 3 The density after graphitization treatment is 0.42 g / cm³. 3 .
[0131] In this embodiment, the metal oxide is CuO, which can partially create pores during the high-temperature heat treatment stage. The roll film will expand slightly during the high-temperature stage and the graphitization stage. Therefore, in this embodiment, when the roll is tightened before entering the high temperature stage, a gap needs to be left for each turn so that the whole roll of graphene foam film obtained after graphitization treatment will not break.
[0132] The graphene thermal conductive film prepared in this embodiment was characterized by SEM and EDS. The results were similar to those in Example 1. There were pores on the film surface and no impurities on the film surface, so the corresponding figures are omitted.
[0133] The graphene thermally conductive film has a thickness of 39 μm, an average pore size of 0.9 μm, and a density of 2.16 g / cm³. 3 The thermal conductivity is 1390 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation steps is 275 m³ / h. 2 .
[0134] Comparative Example 1: Preparation of Graphene Thermal Conductive Film (1) Preparation of graphene oxide slurry 4.278 kg of graphene oxide filter cake (dry basis) was added to deionized water and stirred evenly to obtain 100 kg of graphene oxide slurry.
[0135] The graphene oxide slurry has a solid content of 4.278% and a viscosity of 39000 mPa·s.
[0136] (2) The preparation of graphene oxide roll film is the same as in Example 1.
[0137] (3) Preparation process of graphene foam film The difference between this step and Example 1 is as follows: the winding method is as follows: the gap between each turn of the first 1 / 3 of the roll length is 6cm, the gap between each turn of the middle 1 / 3 of the roll length is 4cm, and the gap between each turn of the outermost 1 / 3 of the roll length is 3cm. After winding, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature range, the roll is tightened with a gap of 3cm between each turn. The rest of this step is the same as in Example 1.
[0138] Measurements showed that the density after low-temperature treatment was 0.42 g / cm³. 3 The density after high-temperature treatment is 0.32 g / cm³. 3 The density after graphitization treatment is 0.23 g / cm³. 3 .
[0139] (4) The preparation steps of the graphene thermal conductive film are the same as in Example 1.
[0140] Testing revealed that the graphene thermal conductive film has a thickness of 42 μm and a density of 2.16 g / cm³. 3 Thermal conductivity 1280 W / (m·K), single furnace capacity during graphitization stage is 120 m³ / s. 2 .
[0141] Comparing Comparative Example 1 with Example 1, it was found that because no metal oxide was added in Comparative Example 1, pores could not be formed during the high-temperature heat treatment stage. Therefore, the roll film expanded at each stage of heat treatment, requiring sufficient gaps during winding to prevent the graphene foam film obtained after graphitization from breaking. This resulted in a significant decrease in the production capacity of the graphene foam film in Comparative Example 1 during the preparation stage. Furthermore, under the same conditions, the addition of metal oxide significantly increased the film density during the heat treatment stage, and the thermal conductivity also improved to some extent.
[0142] Comparative Example 2: Preparation of Graphene Thermal Conductive Film (1) Preparation of graphene oxide slurry 4.608 kg of graphene oxide filter cake (dry basis) was added to deionized water and stirred until homogeneous to obtain 90 kg of graphene oxide dispersion solution; 0.192 kg of ZnO powder was added to 9.808 kg of deionized water and stirred until homogeneous. Figure 4B After that, it is added to the graphene oxide dispersion solution and mixed evenly. Then, it is homogenized and defoamed by a homogenizer to obtain graphene oxide slurry. The final slurry has an overall solid content of 4.8% and a viscosity of 40,000 mPa·s; ZnO accounts for 4% of the final slurry's solid content.
[0143] Figure 4B This shows the dispersion of ZnO in H2O.
[0144] (2) The preparation of graphene oxide roll film is the same as in Example 2.
[0145] (3) Preparation of graphene foam film The difference between this step and Example 2 is as follows: the winding method is as follows: the gap between each turn of the roll is 4.5cm for the first 1 / 3 of the roll length, 3.5cm for the middle 1 / 3 of the roll length, and 2.5cm for the outermost 1 / 3 of the roll length. After winding, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high-temperature zone, the roll is tightened, with a gap of 2.5cm between each turn. The rest of this step is the same as in Example 1.
[0146] Measurements showed that the density after low-temperature treatment was 0.48 g / cm³. 3 The density after high-temperature treatment is 0.35 g / cm³. 3 The density after graphitization treatment is 0.39 g / cm³. 3 .
[0147] In this comparative example, the metal oxide ZnO was added to deionized water, which can partially create pores during the high-temperature heat treatment stage. However, the pore distribution is uneven, and the roll film will also expand slightly during the high-temperature and graphitization stages. Therefore, in this comparative example, when the roll is tightened before entering the high-temperature stage, a gap needs to be left for each turn so that the whole roll of graphene foam film obtained after graphitization treatment will not break.
[0148] (4) The preparation steps of the graphene thermal conductive film are the same as in Example 1.
[0149] SEM characterization analysis of the graphene thermally conductive film revealed uneven pore distribution on the film surface (e.g., Figure 5 As shown in the figure, this phenomenon is caused by uneven dispersion of ZnO in deionized water.
[0150] Figure 5 The surface of the graphene thermally conductive film with added ZnO-H2O dispersion.
[0151] Testing revealed that the graphene thermally conductive film has a thickness of 39 μm, an average pore size of 1.2 μm, and a density of 2.15 g / cm³. 3 The thermal conductivity is 1370 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation process is 195 m³. 2 .
[0152] Comparing Comparative Example 2 with Example 2, it can be seen that dissolving the metal oxide in deionized water reduces the film density during the heat treatment stage compared to dissolving the metal oxide in an aqueous solvent. The thermal conductivity of the resulting graphene thermally conductive film is also reduced, and the pores on the film surface are unevenly distributed.
[0153] Comparative Example 3: Preparation of Graphene Thermal Conductive Film The difference between this comparative example and Example 1 is that: (1) Replace Fe2O3 powder and TiO2 powder with 0.322 kg MgO powder; MgO accounts for 7% of the final slurry solid content.
[0154] (2) The preparation steps of the graphene foam film are as follows: the gap between each turn of the first 1 / 3 of the length of the roll is 6 cm, the gap between each turn of the middle 1 / 3 of the length is 4 cm, and the gap between each turn of the outermost 1 / 3 of the length is 3 cm. After the roll is finished, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature, the roll is tightened with a gap of 2.5 cm between each turn. The remaining steps and parameters are the same as in Example 1.
[0155] The density of the graphene foam film was measured to be 0.43 g / cm³ after low-temperature treatment. 3 The density after high-temperature treatment is 0.31 g / cm³. 3 The density after graphitization treatment is 0.25 g / cm³. 3 .
[0156] The graphene thermally conductive film has a thickness of 40 μm, an average pore size of 1.0 μm, and a density of 2.13 g / cm³. 3 The thermal conductivity is 1390 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation steps is 180 m³. 2 .
[0157] Comparing Comparative Example 3 with Example 1 reveals that when the metal oxide is MgO (i.e., not the metal oxide described in this invention), the decomposition temperature of MgO is too high, making it impossible to create pores at the high-temperature stage described in this invention. Therefore, when preparing the graphene foam film, sufficient gaps need to be left for foaming and expansion so that the whole roll of graphene foam film obtained after graphitization treatment will not break. The single-furnace capacity during the graphene foam film preparation stage is relatively low. Furthermore, the film density decreases significantly during the heat treatment stage, and the thermal conductivity of the resulting graphene thermally conductive film also decreases.
[0158] Comparative Example 4: Preparation of Graphene Thermal Conductive Film The difference between this comparative example and Example 1 is that: (1) Fe2O3 powder accounts for 8% of the final slurry solid content; TiO2 powder accounts for 7% of the final slurry solid content.
[0159] (2) The preparation steps of the graphene foam film are as follows: the gap between each turn of the first 1 / 3 of the length of the roll is 1.3 cm, the gap between each turn of the middle 1 / 3 of the length is 0.8 cm, and the gap between each turn of the outermost 1 / 3 of the length is 0.3 cm. After the winding is completed, a graphite cylinder is placed on the outermost edge of the roll. Before entering the high temperature, the roll film is tightened so that each turn fits perfectly. The remaining steps and parameters are the same as in Example 1.
[0160] The density of the graphene foam film was measured to be 0.86 g / cm³ after low-temperature treatment. 3 The density after high-temperature treatment is 0.74 g / cm³. 3 The density after graphitization treatment is 0.80 g / cm³. 3 .
[0161] The graphene thermally conductive film has a thickness of 41 μm, an average pore size of 1.3 μm, and a density of 2.18 g / cm³. 3 The thermal conductivity is 1440 W / (m·K), and the single-furnace production capacity of the graphene foam film preparation steps is 530 m³. 2 .
[0162] Comparing Comparative Example 4 with Example 1, it can be seen that when the amount of metal oxide added is too large, the amount of pores formed in the high-temperature heat treatment stage is too large, and the film density is high. Although the roll film can be directly tightened to fit each turn perfectly in the high-temperature stage, the roll film does not expand in the high-temperature stage and the graphitization stage, and the whole roll of graphene foam film obtained after graphitization treatment does not break, the average pore size of the obtained graphene thermal conductive film is significantly increased due to the excessive amount of pores, the thermal conductivity is poor, and the thermal conductivity is also reduced.
[0163] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a graphene thermally conductive film, characterized in that: Includes the following steps: (1) Preparation of graphene oxide slurry After the metal oxide powder is evenly dispersed with the aqueous dispersant, it is then mixed evenly with the graphene oxide dispersion solution. Finally, it is homogenized and defoamed to obtain the graphene oxide slurry. (2) Preparation of graphene oxide roll film The graphene oxide slurry from step (1) is coated onto the substrate, dried, and then the graphene oxide film is peeled off from the substrate and rolled up to obtain a graphene oxide roll film. (3) Preparation of graphene foam film The graphene oxide roll film is wound into a circular graphite boat and subjected to low-temperature heat treatment, high-temperature heat treatment and graphitization heat treatment in sequence to obtain a graphene foam film. (4) Preparation of graphene thermal conductive film The graphene foam film is continuously calendered to obtain a graphene thermally conductive film.
2. The preparation method according to claim 1, characterized in that: In step (1), the metal oxide includes one or more of ZnO, MnO, SnO2, Fe2O3, TiO2, MoO2, and CuO, preferably one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2, and most preferably, the metal oxide is Fe2O3 and TiO2 in a molar ratio of 0.9:
1.
3. The preparation method according to claim 1, characterized in that: In step (1), the aqueous dispersant includes at least one of sodium carboxymethyl cellulose, nanocellulose, and polyacrylic acid.
4. The preparation method according to claim 1, characterized in that: In step (1), the content of graphene oxide is 90%-99.9% of the total solid content of the slurry, and the content of metal oxide is 0.1%-10% of the total solid content of the slurry; in the graphene oxide slurry, the final total solid content of the slurry is 3%-6%, and the viscosity is 10000-80000 mPa·s; Preferably, the graphene oxide content is 93%-99% of the total solid content of the slurry, and the metal oxide content is 1%-7% of the total solid content of the slurry; the final total solid content of the graphene oxide slurry is 4.5%-4.8%.
5. The preparation method according to claim 1, characterized in that: In step (2), the gap of the coating is 3500-4000μm, and the coating temperature is 50-60℃.
6. The preparation method according to claim 1, characterized in that: In step (3), When winding, a gap must be left between each turn, and the gap should gradually decrease from the inside to the outside. For example, the gap between each turn in the first 1 / 3 of the roll length is 1.5-3.8cm, the gap between each turn in the middle 1 / 3 of the roll length is 1-2.8cm, and the gap between each turn in the outermost 1 / 3 of the roll length is 0.5-2cm. Before high-temperature heat treatment, the roll film is rewound so that the gap between each turn is 0-2.3cm. Preferably, when the metal oxide is one or more of ZnO, SnO2, Fe2O3, TiO2, and MoO2, during winding, the gap between each turn in the first 1 / 3 of the length of the roll is 1.5-3cm, the gap between each turn in the middle 1 / 3 of the length is 1-2cm, and the gap between each turn in the outermost 1 / 3 of the length is 0.5-1.2cm; before high-temperature heat treatment, the roll film is rewound so that the gap width between each turn is fixed at 0-1.5cm.
7. The preparation method according to claim 1, characterized in that: In step (3), The low-temperature heat treatment is as follows: heat-treating the graphene oxide roll film at 200℃-400℃ for 24-120h, and then naturally cooling it to room temperature; The high-temperature heat treatment is as follows: the graphene oxide roll film is heat-treated at 800℃-1500℃ for 24-120 hours and then naturally cooled to room temperature; The graphitization heat treatment is as follows: the graphene oxide roll film is heat-treated at 2400-3300℃ for 24-120h and then naturally cooled to room temperature.
8. The preparation method according to claim 1 or 7, characterized in that: In step (3), the density of the graphene foam film is: After low-temperature heat treatment, the density is 0.45-0.90 g / cm³. 3 Preferably, after low-temperature heat treatment, the density is 0.50-0.90 g / cm³. 3 ; After high-temperature heat treatment, the density is 0.35-0.80 g / cm³. 3 Preferably, after high-temperature heat treatment, the density is 0.40-0.80 g / cm³. 3 ; After graphitization heat treatment, the density is 0.40-0.80 g / cm³. 3 Preferably, after graphitization heat treatment, the density is 0.45-0.80 g / cm³. 3 .
9. A graphene thermal conductive film, prepared by the preparation method according to any one of claims 1-8.
10. The graphene thermally conductive film according to claim 9, characterized in that: The density of the graphene thermally conductive film is 2.10-2.20 g / cm³. 3 The thermal conductivity is 1350-1650 W / (m·K); preferably 1420-1650 W / (m·K).
Citation Information
Patent Citations
Graphene heat-conducting film and preparation method thereof
CN115072709A